Albizia anthelmintica: HPLC-MS/MS profiling and in vivo anti-inflammatory, pain killing and antipyretic activities of its leaf extract - Sobeh, Mansour; Wink, Michael (Biomedicine & pharmacotherapy, 2019)
In the current work, the phytochemical composition of a leaf methanol extract from Albizia anthelmintica was thoroughly investigated. The antioxidant, anti-inflammatory, analgesic, and antipyretic activities of the extract were investigated. In the carrageenan induced hind paw edema bioassay; the extract significantly reduced the edema thickness in rats and diminished the leukocyte migration to the peritoneal cavity in mice. The extract exhibited central and peripheral anti-nociceptive effects; it significantly decreased the number of acetic acid induced writhes and prolonged the latency time in the hot plate test. The extract showed a substantial antipyretic activity as it decreased significantly the elevated rectal temperature in mice after intraperitoneal injection of Brewer’s yeast. Molecular docking of some major compounds in the extract to COX-1, COX-2 and 5-LOX, enzymes involved in the inflammation cascade, revealed appreciable interactions with the conserved amino acid residues in these target proteins. These findings were confirmed with in vitro enzyme inhibitory assays in which the extract showed IC50 values of 4.11, 0.054, and 1.74 μg/mL towards COX-1, COX-2 and 5-LOX, respectively. The extract displayed solid antioxidant properties as well with a TAC value of 35.13 U/L and EC50of 5.36 μg/mL in DPPH assay. These findings suggested that Albizia anthelmintica is a good antioxidant with potential therapeutic efficacy for treating inflammation, pain and related oxidative stress disorders.